Fungal planet description sheets: 558-624 - P. W. Crous (2018)
© 2017 Naturalis Biodiversity Center & Centraalbureau voor Schimmelcultures. Novel species of fungi described in this study include those from various countries as follows: Australia: Banksiophoma australiensis (incl. Banksiophoma gen. nov.) on Banksia coccinea, Davidiellomyces australiensis (incl. Davidiellomyces gen. nov.) on Cyperaceae, Didymocyrtis banksiae on Banksia sessilis var. cygnorum, Disculoides calophyllae on Corymbia calophylla, Harknessia banksiae on Banksia sessilis, Harknessia banksiae-repens on Banksia repens, Harknessia banksiigena on Banksia sessilis var. cygnorum, Harknessia communis on Podocarpus sp., Harknessia platyphyllae on Eucalyptus platyphylla, Myrtacremonium eucalypti (incl. Myrtacremonium gen. nov.) on Eucalyptus globulus, Myrtapenidiella balenae on Eucalyptus sp., Myrtapenidiella eucalyptigena on Eucalyptus sp., Myrtapenidiella pleurocarpae on Eucalyptus pleurocarpa, Paraconiothyrium hakeae on Hakea sp., Paraphaeosphaeria xanthorrhoeae on Xanthorrhoea sp., Parateratosphaeria stirlingiae on Stirlingia sp., Perthomyces podocarpi (incl. Perthomyces gen. nov.) on Podocarpus sp., Readeriella ellipsoidea on Eucalyptus sp., Rosellinia australiensis on Banksia grandis, Tiarosporella corymbiae on Corymbia calophylla, Verrucoconiothyrium eucalyptigenum on Eucalyptus sp., Zasmidium commune on Xanthorrhoea sp., and Zasmidium podocarpi on Podocarpus sp. Brazil: Cyathus aurantogriseocarpus on decaying wood, Perenniporia brasiliensis on decayed wood, Perenniporia paraguyanensis on decayed wood, and Pseudocercospora leandrae-fragilis on Leandra fragilis. Chile: Phialocephala cladophialophoroides on human toe nail. Costa Rica: Psathyrella striatoannulata from soil. Czech Republic: Myotisia cremea (incl. Myotisia gen. nov.) on bat droppings. Ecuador: Humidicutis dictiocephala from soil, Hygrocybe macrosiparia from soil, Hygrocybe sangayensis from soil, and Polycephalomyces onorei on stem of Etlingera sp. France: Westerdykella centenaria from soil. Hungary: Tuber magentipunctatum from soil. India: Ganoderma mizoramense on decaying wood, Hodophilus indicus from soil, Keratinophyton turgidum in soil, and Russula arunii on Pterigota alata. Italy: Rhodocybe matesina from soil. Malaysia: Apoharknessia eucalyptorum, Harknessia malayensis, Harknessia pellitae, and Peyronellaea eucalypti on Eucalyptus pellita, Lectera capsici on Capsicum annuum, and Wallrothiella gmelinae on Gmelina arborea. Morocco: Neocordana musigena on Musa sp. New Zealand: Candida rongomai-pounamu on agaric mushroom surface, Candida vespimorsuum on cup fungus surface, Cylindrocladiella vitis on Vitis vinifera, Foliocryphia eucalyptorum on Eucalyptus sp., Ramularia vacciniicola on Vaccinium sp., and Rhodotorula ngohengohe on bird feather surface. Poland: Tolypocladium fumosum on a caterpillar case of unidentified Lepidoptera. Russia: Pholiotina longistipitata among moss. Spain: Coprinopsis pseudomarcescibilis from soil, Eremiomyces innocentii from soil, Gyroporus pseudocyanescens in humus, Inocybe parvicystis in humus, and Penicillium parvofructum from soil. Unknown origin: Paraphoma rhaphiolepidis on Rhaphiolepsis indica. USA: Acidiella americana from wall of a cooling tower, Neodactylaria obpyriformis (incl. Neodactylaria gen. nov.) from human bronchoalveolar lavage, and Saksenaea loutrophoriformis from human eye. Vietnam: Phytophthora mekongensis from Citrus grandis, and Phytophthora prodigiosa from Citrus grandis. Morphological and culture characteristics along with DNA barcodes are provided.